Shedding light on the 239Pu fission source term with new high-precision experiments and advanced fission modeling - Neudecker, D.; Lovell, A. E.; Kelly, K. J.; Marini, P.; Snyder, L.; White, M. C.; Talou, P.; Devlin, M.; Taieb, J.; Chadwick, M. B. (Frontiers in Physics, 2023)
In the last decade, there has been a renaissance of fission research resulting in new high-precision experiments and advanced fission modeling. For instance, the Chi-Nu and CEA teams supplied, for the first time, the $^{239}$Pu prompt fission neutron spectrum (PFNS) for broad ranges of incident and outgoing neutron energies. The CEA team also measured $^{239}$Pu average prompt neutron multiplicities, $\overlineν_p$, with lower statistical uncertainties and a technique significantly different than the one used in the past. The NIFFTE collaboration provided $^{239}$Pu\nf/$^{235}$U\nf\ cross section shape ratios with uncertainties below 1% utilizing a novel detector type. Advanced fission event generators were developed, among them CGMF, FIFRELIN, FREYA, and GEF, which calculate post-scission fission observables in a correlated manner. These new experimental data and more consistent fission models change the evaluated PFNS, $\overlineν_p$, and \nf\ cross sections, some only modestly, compared to ENDF/B-VIII.0. In turn, the individual new nuclear data distinctly change simulated effective neutron multiplication factors of fast critical assemblies, but their combined impact is small, while affecting the prediction of LLNL pulsed sphere neutron leakage spectra and reaction rates only within experimental uncertainties. Also, the parameters obtained from fitting to $\overlineν_p$ reproduce various post-scission fission observables within the uncertainties of experimental data. This indicates that new differential experiments and consistent fission modeling reduce compensating errors present in ENDF/B-VIII.0.